Kurikulum Pendidikan Pesantren: Mengurai Pembentukan Karakter Nasionalisme Santri - Ahmad Halid (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
The pesantren (Islamic boarding school) links yellow treatises to necessities of life, including enriching insights and broadening students' understanding of authoritative sources of Islamic teachings (al-qur'an and al-hadith) grounded in the thought of Muslim scholars; madzhab founders whose intellectual and personal values are widely recognized. This research aims to examine "how can curriculum in pesantren nourish the sense of nationalism among santri (students in Islamic boarding school)?” through employing a qualitative approach involving observation, interviews and documentation. Data were analyzed using the Miles and Huberman models. It shows that yellow treatises are regarded as primary resources that give rise to intellectual reflections and scientific traditions as part of Indonesian Muslim identity. Typical knowledge leads to sensitivity of local culture: as a basis for the advancement of Indonesian Muslims prepared to adapt the advancement of science and technology in the future. Islamic boarding schools can nourish students' character, establish the sense of nationalism and promote of specific skills.